Rubber pyrolysis oil as a source of alternative fuel and chemicals - 314275 Md. Kawser Jamil; Farid Nasir Ani, 1957-; Asian Pacific Confederation of Chemical Engineering Congress (8th : 1999 : Seoul, Korea) (Skudai : Universiti Teknologi Malaysia, 1999)
50